El trabajador social y su intervención con familias víctimas de violencia doméstica en tiempos de covid del sector Bellavista - Saraguro Ramírez, Nadia Katherine (My University, 2020)
This research work details a brief analysis on family violence, which is without a doubt the expression of abuse or mistreatment that negatively influences the dynamics and communication of its members, it is also intended to make known the performance of the Social Worker who has been very present in the health emergency of Covid-19, by providing the necessary support to victims of domestic violence, a complex situation that is aggravated within the family nucleus as a result of the confinement, and the social distancing caused by the pandemic. The general objective of this research is to define the role of the social worker with families who are victims of domestic violence in times of covid in the Bellamaria sector, taking into account that the family is the primary support of every individual for the development of their qualities and skills in the society, therefore the role of the social worker is that of mediator, which implies a way to help the family to find a response to the new circumstances to resolve their indifference and strengthen good relationships, thus avoiding any type of judicial process, It is carried out based on a psychoanalytic approach, giving way to the subject to know those internal problems that do not facilitate him or her to reach emotional and social maturity. The methodology applied in the research is of a bibliographic nature from various scientific platforms, which provides a relevant subject to the analysis and criteria of the author, allowing him to obtain updated information on the specialized actions of the social worker.
El presente trabajo de investigación detalla un breve análisis sobre la violencia doméstica que es sin lugar a duda la expresión de abuso o maltrato que influye negativamente la dinámica y comunicación de sus integrantes, también se pretende dar a conocer la actuación del Trabajador Social que ha estado muy presente ante la emergencia sanitaria del Covid-19, al proporcionar el apoyo necesario a las víctimas de violencia doméstica, situación compleja que se agrava al interior del núcleo familiar a consecuencia del encierro, y el distanciamiento social provocado por la pandemia. El objetivo general de esta investigación es definir el rol del trabajador social con familias víctimas de violencia doméstica en tiempos de Covid del sector Bellavista, tomando en cuenta que la familia es el soporte primordial de todo individuo para el desarrollo de sus cualidades y habilidades en la sociedad, por ello el rol que cumple el trabajador social es el de mediador, el cual implica una forma de ayudar a la familia a encontrar respuesta a las nuevas circunstancias para resolver sus diferencias y fortalecer buenas relaciones, evitando así cualquier tipo de proceso judicial, está realizada con base a un enfoque psicoanalítico dándole paso al sujeto a conocer aquellos problemas internos que no le facilitan alcanzar la madurez afectiva y social. La metodología aplicada en la investigación es de carácter bibliográfica de diversas plataformas científicas, que le proporciona una temática relevante al análisis y criterio del autor, permitiéndole obtener información actualizada sobre el accionar especializada del trabajador social.
Keywords: VIOLENCIA; COVID; FAMILIA; TRABAJO SOCIAL